In-medium spectral functions of vector- and axial-vector mesons from the functional renormalization group - Jung, Christopher; Rennecke, Fabian (Physical review, 2017)
In this work, we present the first results on vector- and axial-vector meson spectral functions as obtained by applying the nonperturbative functional renormalization group approach to an effective low-energy theory motivated by the gauged linear sigma model. By using a recently proposed analytic continuation method, we study the in-medium behavior of the spectral functions of the ρ and a1 mesons in different regimes of the phase diagram. In particular, we demonstrate explicitly how these spectral functions degenerate at high temperatures as well as at large chemical potentials, as a consequence of the restoration of chiral symmetry. In addition, we also compute the momentum dependence of the ρ and a1 spectral functions and discuss the various timelike and spacelike processes that can occur.